Ultrathin ultrananocrystalline diamond film synthesis by direct current plasma-assisted chemical vapor deposition - Lee, Hak-Joo; Jeon, Hyeongtag; Lee, Wook-Seong (AMER INST PHYSICS, 2011)
The synthesis of ultrathin, mirror-smooth, and void-free ultra-nanocrystalline diamond (UNCD) film was investigated using DC-PACVD. The seeding process was investigated in the previously reported "two-step" seeding scheme, where the substrate was pretreated in microwave hydrocarbon plasma prior to the ultrasonic seeding to enhance seed density; in the present study, DC plasma and hot filament process were adopted for the pretreatment, instead of the conventional microwave plasma. Two types of nano-diamond seed powders of similar grain sizes but with different zeta potentials were also compared. The pretreated substrate surface and the synthesized UNCD film were characterized by near edge x-ray absorption fine structure, FTIR, AFM, high-resolution scanning electron microscope, HR-TEM, and Raman spectroscopy. The electrophoretic light scattering spectroscopy was adopted to characterize the zeta potentials of the seeding suspensions and that of the substrates, respectively. Contrary to the previous report, the pretreatments deteriorated the seed density relative to that of the non-treated substrate. By contrast, the seed density was drastically improved by using a proper type of the nano-diamond seed powder. The seed density variation according to the substrate pretreatments and the type of the seed powders was attributed to the relative values of the zeta potentials of the substrates and that of the seed powders, which indicated the electrostatic nature of the seeding process. The variation of the substrate surface zeta potentials was attributed to the variation in the surface terminations induced by the respective pretreatments. The present DC-PACVD environment ensured that the secondary nucleation was also active enough to generate the densely packed UNCD grains in the growth stage. Consequently, the ultrathin, mirror-smooth and void-free UNCD film of 30 nm in thickness was enabled. (C) 2011 American Institute of Physics. [doi:10.1063/1.3652752]